Associations Between Placental Corticotropin–Releasing Hormone, Maternal Cortisol, and Birth Outcomes, Based on Placental Histopathology - Johnston, Robert C.; Faulkner, Megan; Carpenter, Philip M.; Nael, Ali; Haydel, Dana; Sandman, Curt A.; Wing, Deborah A.; Davis, Elysia Poggi (Reproductive sciences (Thousand Oaks, Calif.), 2020)
Preterm birth remains the leading cause of neonatal morbidity and mortality, with complex biochemical pathways requiring continued understanding and assessment. The objective of this study is to assess the associations between maternal cortisol and placental corticotropin–releasing hormone (placental CRH) concentrations with birth outcomes when stratified by placental histopathology. We conducted an analysis of 112 singleton pregnancies who received betamethasone between 23 and 34 weeks’ gestation. Maternal blood and saliva were collected prior to betamethasone administration and samples assayed for plasma cortisol (pCort), salivary cortisol (sCort), and placental CRH levels. Placental findings were characterized as inflammatory, maternal vascular underperfusion (MVU), or no pathology, and compared for the outcomes of placental CRH, pCort, and sCort levels, gestational age at birth (GAB), and birthweight percentiles (BWP). Thirty-six subjects were characterized as inflammatory, 38 as MVU, and 38 without placental abnormalities. Histopathology groups differed significantly on placental CRH levels, GAB, and BWP. Post hoc tests suggested that the MVU group had higher placental CRH than the inflammatory or no pathology groups, and despite delivering earlier than the other two groups, the inflammatory group had infants with significantly higher BWP. No differences existed between groups in terms of mean plasma or sCort levels. Higher placental CRH and pCort levels were associated with earlier GAB in the overall sample, but when split by group, these associations remained significant only among the MVU group. Higher placental CRH was also associated with lower BWP in the overall sample but did not remain significant when split by group. Higher sCort was associated with lower BWP only in the MVU group. There is differentiation of placental CRH, cortisol, and birth outcomes when evaluated by placental histopathology. This highlights the importance of evaluating birth outcomes within the context of placental histopathology.